SAT0187 The Antimicrobial Peptide LL-37 and Type I Interferon in Idiopathic Inflammatory Myopathies. (15th July 2016) - Lu, X.; Tang, Q.; Lindroos, E.; Lindh, M.; Agerberth, B.; Lundberg, I.; Wick, C.
Abstract : Background: The human antimicrobial peptide LL-37, exhibits a variety of biological functions such as activation of plasmacytoid dendritic cells (pDC) to produce type I interferon and mediate tissue damage. In autoimmune diseases such as systemic lupus erythematosus, rheumatic arthritis, and psoriasis LL-37 released by neutrophils is overexpressed at inflammatory sites and may have a role in pathogenesis by induction of type I interferon pathway. Type I interferon pathway is activated in subgroups of patients with idiopathic inflammatory myopathies (IIM). The mechanisms that drive type I interferon in IIM is unclear. We hypothesized that LL-37 in muscle and/or skin may be a factor that can activate type I interferon in these conditions. Objectives: The aim of our study was to investigate the expression of LL-37 and type I interferon related proteins (MxA) in the affected organs of patients with polymyositis (PM) and dermatomyositis (DM). Methods: Twelve muscle and 5 skin biopsies were obtained from 6 PM and 6 DM patients. Additional 3 skin biopsies taken from non-affected skin in 3 of DM patients. Five muscle and 7 skin biopsies from healthy subjects were selected as controls (HC). Immunohistochemistry staining of LL-37, CD66b (neutrophil), MxA (type I interferon), BDCA-2 (pDC), CD68 and CD163 (both macrophage markers) were performed in all muscle and skin specimens. Western blot (WB) was utilized to confirm the expression of LL-37 in muscle and skin tissues. Co-localization of LL-37 and neutrophils in muscle and skin tissue was confirmed by double-staining. The relationship of the markers were analyzed and compared with the clinical features of PM/DM patients. Results: The expression of LL-37, CD66b, BDCA-2, and MxA in muscle as well as in skin tissue was significantly higher in PM/DM patients when compared to HC (P<0.05). In addition, LL-37 expression in skin lesions of DM patients was higher than in non-affected skin from the same patient (P<0.05). WB confirmed LL-37 expression in muscle and skin tissues of PM/DM patients but was negative in HC. A positive correlation was found between expression of LL-37 and CD66b in muscle and skin tissues of PM/DM patients (R=0.89 and 0.69 respectively, P<0.05). Double-staining revealed co-localization of LL-37 and neutrophils in both muscle and skin tissues. The expression of CD66b correlated to MxA expression in muscle tissue in PM/DM patients (R=0.58, P<0.05). Expression of LL-37 and CD66b in muscle tissue correlated to serum CK levels (R=0.85 and 0.88 respectively, P<0.05). LL-37 and CD66b expression in skin tissue correlated with disease activity (physician global assessment score) in DM patients. Conclusions: The presence of the antimicrobial peptide LL-37 in affected muscle and skin tissues of patients with PM and DM together with the correlation of expression of LL-37 to the type I inducible protein MxA might indicate a role of LL-37 as an inducer of interferon production in patients with PM and DM. Thus, LL-37 may be involved in the pathogenesis of these diseases. References: Hoffmann MH, Bruns H, Bäckdahl L, et al. The cathelicidins LL-37 and rCRAMP are associated with pathogenic events of arthritis in humans and rats. Ann Rheum Dis. 2013 Jul;72(7):1239–48. Disclosure of Interest: None declared